20.3 DNA METHYLATION PROFILING MIGHT SHED LIGHT ON THE BIOLOGY OF CANNABIS ASSOCIATED PSYCHOSIS. (9th April 2019) - Di Forti, Marta; Dempster, Emma; Quattrone, Diego; Tripoli, Giada; Kandaswamy, Radhika; Morgan, Craig; Os, Jim van; Rutten, Bart; Murray, Robin; Mill, Jonathan; Wong, Chloe; Radhakrishnan, Rajiv
Abstract: Background: Epigenetic mechanisms are emerging as potential important players that underlie the interactions between genetic and environmental risk factors in the aetiology of psychiatric disorders. Cannabis is the most widely used recreational drug and its use, with a dose relationship pattern, has consistently been associated with an increased risk to develop Psychotic Disorders. Consistent with animal data, it has been shown that regular cannabis users show higher levels of CB1 mRNA expression and promoter methylation status in peripheral blood cells than non-users. We are the first to investigate if cannabis use leaves a distinct DNA methylation signature across the genome and if this overlaps with biological pathways already associated with Psychotic Disorders. Methods: Genome-wide DNA methylomic (EWAS) profiling using the Illumina Infinium MethylationEPIC array in human peripheral blood tissue from 413 First episode Psychosis and 521 healthy population controls part of the EUGEI (European network of national schizophrenia networks studying Gene-Environment Interactions) study. Samples were randomized with respect to phenotypic status, age, sex and study site to avoid batch effects. Stringent QC pipeline checks (i.e. signal intensity, duplicates, sex, bisulphite conversion, genotypes) with cross-reactive and non-reliable probes removed. Our analyses focused on probes with a minimum range of methylation values of 5% within the middle 80% of samples, resulting in 618, 048 probes5. Covariates: 1) tobacco smoking score; 2) age; 3) cell type proportions and 4) study sites Linear model was used to compare across the DNA methylomic profiling of a) Lifetime cannabis users (YES) and b) daily cannabis users with never users. Results: Our preliminary analyses revealed regular cannabis use-associated dysregulation of DNA methylation at multiple loci across the epigenome that also include CpGs previously associated with Schizophrenia. Downstream pathway analysis revealed enrichment of genomic regions that are highly disease relevant. Conclusions: Our preliminary findings in a sample of healthy controls suggest: Difference in DNA Methylation profiling between individuals who have tried cannabis at some point in their life and more significantly so in daily users compared to never users; 2) these differences were detected taking into account important confounders including the epigenetic tobacco scoring. Most of these DMS are in protein coding genes including BDNF, SHANK2 and CACNA2D2, which are involved in important neurodevelopmental processes. BDNF and CACNA2D2 have also been indicated as susceptibility genes for Schizophrenia and Bipolar Disorders. Finally, our pathway analysis indicated significant enrichment for these DMSs in pathways involved in biological processing such as neuronal migration and development and glutamate receptor binding, a possible hint towards the unravelling of the biology linking adolescence cannabis use with psychosis.